(untitled) (Journal of Oriental Studies, 2019)
The aim of the study is to develop teaching methods for future teachers of foreign languages based on the use of digital educational resources. In the case of the formation of digital resources of the infor mation society to improve the quality of teaching a foreign language, an analysis of the literature revealed the following contradictions: between a person, society, the state and the needs of the labor market and the education system in the context of traditional knowledge in accordance with the characteristics of the current dissatisfaction with the quality of higher education; an increase in the information that deter mines the content of foreign teacher education, and the definition of a limited period of study and the possibilities of subjects of the educational process. Because of the above, the relevance of learning a for eign language through the introduction of digital educational disciplines is questionable, since this field has not been sufficiently studied. The urgency of the tasks, its theoretical significance and the lack of practical development in pedagogy led to the discovery of the subject. Our research is based on the fol lowing literature: Theoretical aspects of the use of digital resources in the field of education. P.F.Sysoyev,M.N. Evstigneyev, A.N. Tikhonov, V.P. Tikhomirova, E.S. Polat, I.V. Robert and many other research ers. The conceptual basis of informatization of education and the use of digital resources in the field of education in Kazakhstan in various pedagogical specialties G.K. Nurgaliyeva, D.M. Dzhusubalieva, E.V. Artукbayeva, A.T. Chaklikova and many others are mentioned in the works of scientists. Key words: Computer, Digital Resources in Education, ICT, Foreign language, Cognitive Process, Communication, Information Technology, Internet, Educational Services, Pedagogical Programs.